Detection of bacteria, viruses, parasites and fungi bioterrorism prevention - NATO Advanced Research Workshop on Detection of Bacteria, Viruses, Parasites and Fungi (NATO Science for Peace and Security Series A: Chemistry and Biology, 2010)
This publication represents the result of the fruitful workshop organised with the aim to attract the attention on the possibility of bio terrorism attack, with the s- port of NATO funds. In the last years the attention was strongly concentrated on the terrorism view similar to “military type attacks:” bomb on the trains, kamikazes, airplanes etc. As consequence many devices studied are directed to prevent these attacks such as the control of the passengers before the flight. For the people terrorism is therefore equivalent to bomb or similar and nobody think that there is also other possible and sophisticated means that can be used by the terrorist. In 1995 Sarin gas in the Tokio subway killed 12 people and affected 5,000 persons. In the USA anthrax was sent by mail to many federal offices. These events and other cases attract the attention on these possible terrorist attacks and the first recommendations for preventing theses events were\elaborated in the United State and in Europe. The possible agents and the modality that can be used for the diffusion are analysed and food and water are considered the principal and more favourable way. The story and the principal decision about this were reported in the first article of this collection which introduces the concept of bio-terrorism. BIOTERRORISM PREVENTION -- Bioterrorism: A Potential Weapon for Terrorist Attacks Through Food and Water Contamination: Evolution of Our Understanding of the Use of Chemical and Bacteriological Weapons -- Detection and Quantification of Bacteria and Fungi Using Solid-Phase Cytometry -- Vulnerability Assessment and Mapping of Akounq Groundwater Body, Armenia -- BACTERIA DIAGNOSTIC TESTS -- Methods for Detection of Shiga-Toxin Producing Escherichia coli (STEC) -- Genetic Diversity of Enterococci in Bryndza Cheese -- Salmonella Infections -- Molecular Diagnostics of Staphylococcus aureus -- Molecular Methods to Detect Bacillus cereus and Bacillus thuringiensis in Foods -- Control of Listeria monocytogenes in San Daniele Dry Cured Ham by Different Technologies: Reduction of L. Monocytogenes in Dry Cured Ham -- VIRAL INFECTIONS -- Epidemiology and Diagnosis of Hepatitis B in the Mediterranean Region and Elsewhere -- Hepatitis E Virus (HEV) – An Emerging Viral Pathogen -- Dengue Virus Diagnostics -- PARASITES AND FUNGI -- Infectious Forms of Parasites in Food: Man Embedded in Ecosystems -- Unusual Developmental Pattern of Expression of Enzymes Involved in DNA Biosynthesis in Trichinella spiralis and Trichinella pseudospiralis -- Immunodulation and Helminths: Towards New Strategies for Treatment of Immune-Mediated Diseases? -- Parasites and Oncogenesis with a Special Reference to Gastro-Intestinal Neoplasia Induced by Cryptosporidium parvum -- Smart Biosensors for Determination of Mycotoxines.